Fiscal Distress: The Role of Budget Policy in Local Government - Robinson Robinson; Vika Fitranita; Ratih Astiakurnia Putri; Andi Ihsan Triputrajaya; Irman Puansah (Institut Bisnis dan Informatika Kesatuan, 2025)
Fiscal distress in local governments, particularly in South Sumatra, poses a significant challenge to delivering public services due to limited financial capacity. This study aims to examine the impact of budget policies, specifically surplus or deficit and solvency, on fiscal distress, using the stakeholder theory to understand how local governments adapt to central government funding pressures. The research employs a quantitative approach, analyzing data from 65 local governments in South Sumatra from 2020 to 2023, totaling 260 observations. Logistic regression is used to test the effect of budget deficit policy and three solvency ratios (operational, employee expenditure, and total budget solvency) on fiscal distress, measured by the regional fiscal capacity ratio. The findings show that 58% of local governments experienced fiscal distress, with budget deficits significantly increasing the likelihood of distress, while operational budget solvency significantly reduces it. Employee expenditure and total budget solvency show no significant effect, likely due to mandatory spending regulations. The study concludes that effective budget management, through realistic revenue projections and optimized operational expenditures, is crucial for mitigating fiscal distress, offering practical guidance for local governments to enhance financial stability.